The Inspiring English Lecturers of the English Education Department at IAIN Samarinda - Alfisah Alfisah; Umar Fauzan (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2019)
The successful of teaching and learning process is cannot be separated from the lecturers' role that inspiring the students. An inspiring English lecturer should be possessed at least three skills namely attitudinal skills, teaching technical strategy, and students’ changes in learning English. In teaching strategy skills, it has the other indicators of being an inspiring English lecturer such as a) preparation; b) planning and development curriculum; c) use curriculum framework; d) clear targets and objectives of teaching; e) developing strategy and planning activities of teaching; f) designs of appropriate learning modules; g) planning classroom activities; h) finding new innovative teaching strategies; i) finding newest references; j) good classroom management. In teaching strategy to university students, the lecturer should be more interesting, creative and able to keep the students away from getting bored. In order to keep the students' away from getting bored in learning English, the lecturers had to use good teaching strategy. The objectives of this research are: (1) to know the teaching plan of the English lecturers based on teaching strategy; (2) to the teaching implementation of the English lecturers based on teaching strategy in English Education department. The design of this research is descriptive qualitative. The subject of this research is English Education Department of IAIN Samarinda. In this study, the researcher used a questionnaire guide and an observation sheet. The result of this research is that all of the lecturers of English Department of IAIN Samarinda is an inspiring person who always prepares the lessons well. This indicates that all students of English Education Department of IAIN Samarinda more appreciation with the statement. Meanwhile, the statement that shows the lowest responses is found on the statement of an English lecturer should think hard to find the latest references in their instructions. This indicates that a huge number of these indicators had not yet owned by IAIN English lecturers Samarinda.